The Pricing of Credit Default Swaps During Distress - Singh, Manmohan; Andritzky, Jochen (Washington, D.C. : International Monetary Fund, 2006)
Credit default swaps (CDS) provide the buyer with insurance against certain types of credit events by entitling him to exchange any of the bonds permitted as deliverable against their par value. Unlike bonds, whose risk spreads are assumed to be the product of default risk and loss rate, CDS are par instruments, and their spreads reflect the partial recovery of the delivered bond's face value. This paper addresses the implications of the difference between bond and CDS spreads and shows the extent to which the recovery assumption matters for determining CDS spreads. A no-arbitrage argument is applied to extract recovery rates from CDS and bond markets, using data from Brazil's distress in 2002-03. Results are related to the observation that preemptive restructurings are now more common than straight defaults in sovereign bond markets and that this leads to a decoupling of CDS and bond spreads.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet